Design and synthesis of an N-benzyl 5-(4-sulfamoylbenzylidene-2-thioxothiazolidin-4-one scaffold as a novel NLRP3 inflammasome inhibitor. (1st June 2022) - Zuo, Dongxu; Do, Nayeon; Hwang, Inhwa; Ann, Jihyae; Yu, Je-Wook; Lee, Jeewoo
Graphical abstract: Abstract: A series of N -benzyl 5-(4-sulfamoylbenzylidene-2-thioxothiazolidin-4-one analogs, designed as hybrids of CY09 and JC121, were investigated as inhibitors of NLRP3 inflammasome activation. Among them, compounds 34 and 36 were identified as promising NLRP3 inhibitors by measuring the amount of active caspase-1 p20 and IL-1β produced by NLRP3 inflammasome activation. Further studies indicated that both compounds inhibited NLRP3 inflammasome assembly by reducing the formation of NLRP3 and ASC oligomer specks and selectively inhibited only NLRP3 inflammasome activation and not other inflammasomes such as NLRC4 and AIM2.